2009
DOI: 10.1105/tpc.108.062513
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fatty Acyl-CoA Synthetase Is Required for Pollen Development and Sporopollenin Biosynthesis inArabidopsis   

Abstract: Acyl-CoA Synthetase (ACOS) genes are related to 4-coumarate:CoA ligase (4CL) but have distinct functions. The Arabidopsis thaliana ACOS5 protein is in clade A of Arabidopsis ACOS proteins, the clade most closely related to 4CL proteins. This clade contains putative nonperoxisomal ACOS enzymes conserved in several angiosperm lineages and in the moss Physcomitrella patens. Although its function is unknown, ACOS5 is preferentially expressed in the flowers of all angiosperms examined. Here, we show that an acos5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
248
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 253 publications
(259 citation statements)
references
References 71 publications
(158 reference statements)
10
248
1
Order By: Relevance
“…botany.utoronto.ca/efp/cgi-bin/efpWeb.cgi) (Winter et al, 2007), to determine the tissue expression patterns of At4g35420 (DRL1) and At1g68540 (CCRL6). The results of this search indicated that both were preferentially expressed in young flower buds, in accordance with their high coregulation scores, similar to the expression patterns reported for PKSA, PKSB, and ACOS5 (de Azevedo Souza et al, 2009;Kim et al, 2010). To facilitate their designation in the following paragraphs, genes corresponding to At4g35420 (DRL1) and At1g68540 (CCRL6) were named TET-RAKETIDE a-PYRONE REDUCTASE1 (TKPR1) and TKPR2, respectively, in anticipation of the enzymatic activities described below for the two corresponding proteins.…”
Section: At4g35420 and At1g68540 Expression Profiles During Flower Desupporting
confidence: 59%
See 4 more Smart Citations
“…botany.utoronto.ca/efp/cgi-bin/efpWeb.cgi) (Winter et al, 2007), to determine the tissue expression patterns of At4g35420 (DRL1) and At1g68540 (CCRL6). The results of this search indicated that both were preferentially expressed in young flower buds, in accordance with their high coregulation scores, similar to the expression patterns reported for PKSA, PKSB, and ACOS5 (de Azevedo Souza et al, 2009;Kim et al, 2010). To facilitate their designation in the following paragraphs, genes corresponding to At4g35420 (DRL1) and At1g68540 (CCRL6) were named TET-RAKETIDE a-PYRONE REDUCTASE1 (TKPR1) and TKPR2, respectively, in anticipation of the enzymatic activities described below for the two corresponding proteins.…”
Section: At4g35420 and At1g68540 Expression Profiles During Flower Desupporting
confidence: 59%
“…Therefore, considering the fact that these two putative oxidoreductase genes are tightly coexpressed with ACOS5 and the polyketide synthases PKSA and PKSB in tapetal cells during pollen development (Figures 1 and 2) (de Azevedo Souza et al, 2009;Kim et al, 2010), we examined the possibility that these enzyme activities could function in a common biochemical pathway. Particularly, the tri-and tetraketide compounds produced No amplicon was detectable in tkpr1-1, tkpr1-2, and tkpr2-1 samples, whereas a weak signal was recorded in tkpr2-2 buds, using primers shown in Supplemental Table 1 online.…”
Section: Enzymatic Activities Of Tkpr1 and Tkpr2 Proteins Produced Inmentioning
confidence: 99%
See 3 more Smart Citations